American fauna of Cerambycidae and Disteniidae (Coleoptera): new species, new records, and notes - Heffern, Daniel; Santos-Silva, Antonio (Zootaxa, 2023)
Sexual dimorphism in Elaphidion scabricolle (Bates, 1872) (Cerambycidae, Cerambycinae, Elaphidiini) is reported and the inclusion of the species in this genus is questioned. Leptostylus bicolor sp. nov. (Cerambycidae, Lamiinae, Acanthocinini) is described from Panama. Leptostylus pygialis Bates, 1872 is redescribed based on a female with an elytral pubescent pattern different from that of the lectotype; the sex of the lectotype, originally reported as female is commented on. Notes are provided on Lophopoeum saronotum Bates, 1872 (Cerambycidae, Lamiinae, Acanthocinini). Distenia (Basisvallis) phaeocera Bates, 1880 (Disteniidae) is recorded from Panama and Drycothaea sallei Thomson, 1868 (Cerambycidae, Lamiinae, Calliini) is recorded from Mexico (Chiapas) and Honduras.